Relationship of Load and Backpack Height with Lower Back Pain Among X Senior High School in Tangerang - Hartanto Hartanto; Santoso Gunardi; Mira Fitriningsih; Gracecaella Arjanti Dwiningrum (Jurnal MedScientiae, 2023)
Lower back pain increases by 10% -50% by school age. The use of backpacks such as backpack weights and height can affect lower back pain. Increased backpack weight can compress the lumbar intervertebral discs. The position of the backpack is too low will tend to make students lean forward. This happens because students try to balance the center of gravity. Research objective is to investigate load and backpack height with lower back pain among X Senior High School in Tangerang in 2019. A total of 76 children, ages 14 to 17 years. Each student’s body weight, height, backpack height, average backpack load for 5 days were measured, and filled out questionnaire sheets. Students who have complaints of low back pain will interpret on a scale of 0-10. The results obtained are then analyzed and interpreted. There is a relationship between backpack bag weight with low back pain in Tangerang X High School students (sig. 2-sided) <0.05), but there is no relationship between backpack height and low back pain in Tangerang X High School students (sig. 2- sided)> 0.05). The conclusion is the backpack weight significantly associated with low back pain. Meanwhile, backpack height does not significantly associated with low back pain.